Differential pathological changes in colon microenvironments in acute and chronic mouse models of inflammatory bowel disease - NaYeon Ham; Minji Park; Young-An Bae; Eui-Ju Yeo; YunJae Jung (Animal Cells and Systems)
Inflammatory bowel disease is a chronic condition characterized by inflammation of the gastrointestinal tract, resulting from an abnormal immune response to normal stimuli, such as food and intestinal flora. Since the etiology of this disease remains largely unknown, murine models induced by the consumption of dextran-sodium sulfate serve as a pivotal tool for studying colon inflammation. In this study, we employed both acute and chronic colitis mouse models induced by varying durations of dextran-sodium sulfate consumption to investigate the pathological and immunologic characteristics throughout the disease course. During the acute phase, activated innate inflammation marked by M1 macrophage infiltration was prominent. In contrast, the chronic phase was characterized by tissue remodeling, with a significant increase in M2 macrophages and lymphocytes. RNA-sequencing revealed genetic changes in acute and chronic colitis, marked by the maintenance of genomic integrity in the acute phase and extracellular matrix dynamics in the chronic phase. These phase-specific alterations reflect the multifaceted physiological processes involved in the initiation and progression of inflammation in the large intestine, underscoring the necessity for distinct experimental approaches for each phase. The findings demonstrate that the factors shaping the large intestinal immune microenvironment change specifically during the acute and chronic phases of experimental inflammatory bowel disease, highlighting the importance of developing therapeutic strategies that align with the disease course.